Irisin Regulating Skeletal Response to Endurance Exercise in Ovariectomized Mice by Promoting Akt/β-Catenin Pathway - Zhao, Renqing; Zhou, Yalan; Li, Jinqiao; Lin, Junjie; Cui, Wei; Peng, Yan; Bu, Wenqian (Frontiers in Physiology, 2021)
Purpose: Thought irisin is recognized as a pivotal modulator for bone formation, its role in regulating skeletal response to exercise training remains unknown. Therefore, we aimed to determine the change of irisin in response to 8-week exercise training and its role in regulating the effects of exercise on bone loss in ovariectomized (Ovx) mice. Methods: Forty 3-month old female C57BL/6 mic were randomly allocated into four groups: (1) Sham-operated (Sham); (2) ovariectomized; (3) Ovx plus 8-week downhill running exercise (Ex); (4) Ovx plus exercise and received twice weekly injection of cyclo RGDyk protein (a putative anti-irisin receptor agents) (ExRg). Results: Ex group showed enhanced cortical and trabecular volumetric bone mineral density (vBMD) (p<0.05), improved bone microarchitecture, and increased intensity of alkaline phosphatase positive (ALP+) cells compared with Ovx group. However, cyclo RGDyk administration weakened the exercise-related improvement of vBMD, BV/TV, and ALP intensity in bone. Serum estradiol, irisin, and bone alkaline phosphatase were higher, whereas circulating tartrate-resistant acid phosphatase was lower in Ex group compared with Ovx group (p<0.05). Exercise promoted mRNA expression of fibronectin type III domain-containing protein 5 (FNDC5), Akt and ß-catenin, and enhanced protein levels of FNDC5, the ratio of phosphorylated Akt (p-Akt) to Akt, and ß-catenin (p<0.05). When irisin pathways were blocked with cyclo RGDyk, increment of Akt, p-Akt/Akt, and ß-catenin in Ex mice were attenuated. Conclusion: It is suggested that irisin plays a potential role in regulating skeletal response to exercise partly through its interaction with Akt/ß-catenin pathways.